Enablers and Barriers of Healthcare Services for Community-Dwelling Elderly in Rural Indonesia: A Qualitative Evidence Synthesis - Budi Aji; Siti Masfiah; Dian Anandari; Arih Diyaning Intiasari; Dyah Anantalia Widyastari (Karger Publishers, 2023)
Introduction: Healthcare services for elderly populations in Indonesia have been arranged in both institutional and community services. However, only a small number of elderly individuals reside in this residential aged care home setting because of cultural norms in Indonesian communities. Poor health infrastructure is still the main constraint, particularly in rural communities, although they have the adequate social capital to deal with restrictions. It is important to explore the existing implementation of healthcare services for elderly populations in rural Indonesia to shed light on appropriate policy interventions. This review aimed to identify and synthesize relevant evidence in Indonesia regarding the barriers and enablers of healthcare for elderly individuals in rural settings. Methods: This study used a qualitative evidence synthesis method. The search strategy aimed to locate published studies. An initial limited search of PubMed, Web of Science, ScienceDirect, Embase, PsycINFO, and CINAHL was conducted to identify articles on the topic that were published in English from 2010 to 2020. A meta-aggregation approach was used to pool qualitative study findings, employing JBI SUMARI software. Results: Four synthesized statements emerged from the study analysis: (1) integration needs among institutional and community-based healthcare for elderly people in rural areas, (2) the quality of integrated health services for elderly populations must be improved, (3) community support will improve and ensure the sustainability and implementation of community-based healthcare for elderly populations, and (4) community and family awareness must be improved to support care for the elderly. These were substantial insights that can be used to address key challenges in existing healthcare services and improve the system by considering specific features of enablers and barriers. Conclusion: A collaboration between communities, healthcare institutions, families, and government authorities was needed to support the success of the program and maintain the sustainability of services, which will result in adequate healthcare for the elderly population and improved health overall in rural Indonesia.